Prevalence Of Cryptosporidiosis In Buffaloes In And Around Bhubaneswar, Odisha - Mohanty, B.N.; Panda , M.R. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
Faecal samples collected from 305 buffaloes (89 diarrheic and 216 non diarrheic) of different age and sex from Bhubaneswar and adjacent areas of Cuttack and Puri district were examined during a period of three years. Cryptosporidial oocysts were detected in 76 (24.92%) faecal samples . Prevalence of cryptosporidiosis was higher in diarrheic than non diarrheic buffaloes. Significant variation was observed in prevalence between diarrheic and non-diarrheic buffaloes (P<0.05). Highest prevalence was observed in the calves aged below one month followed by calves aged 1 - 3 months of age, 3 months to 1 year and lowest prevalence was observed in the buffaloes aged more than 1 year. Cryptosporidiosis was found to be more prevalent among male than in female buffaloes. Highest percentage of prevalence was recorded in summer season (March-June) followed by Rainy (July-October) and lowest in Winter (November-February).